GLYCOGEN, GLUCOSE, PYRUVATE, LACTATE AND TOTAL PROTEIN CONTENTS IN NYMPHAL ABDOMINAL AND METATHORACIC SCENT GLANDS OF CYCLOPELTA SICCIFOLIA WESTWOOD (HETEROPTERA : PENTATOMIDAE) - SAGAR, CH. VIDYA; JANAIAH, C.; RAVINDER, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The glycogen, glucose and pyruvate contents are more in the metathoracic scent glands of adults than in the abdominal scent glands of nymphal Cyclopelta siccifolia but lactate and total protein contents are higher in the nymphal abdominal scent glands than in the metathoracic glands of adults. These biochemical parameters indicate different metabolic rates for the insect survival.